In the age of rending: Tension and retransformation of cultural identity in the domains of globalization - Canaza-Choque, Franklin Américo (2022)
This study attempts to make a brief overview the impacts reproduced by globalization under the imponderable assumptions that it is, for the present, an endless agency that, inside and outside of it, realizes that the flaws and irregularities that arise they delimit and strain the notion of cultural identity. In this way, through a theoretical model tour, it can be defined that the globalizing impact causes the recognition of two replication movements. On the one hand, in the face of homogenizing impulses, the dimension of interculturality for small cultural groups needs to break with the privileged divide between the global and local. On the other hand, in a space fractured by structural problems, where the State seems to disappear for some minority groups, the effect radiates a partial or total disarmament or disappearance of the latter that, finally, ends up causing a tear in the denotative of cultural identity.